2009
DOI: 10.1073/pnas.0904361106
|View full text |Cite
|
Sign up to set email alerts
|

Selective engagement of G protein coupled receptor kinases (GRKs) encodes distinct functions of biased ligands

Abstract: CCL19 and CCL21 are endogenous agonists for the seven-transmembrane receptor CCR7. They are equally active in promoting G protein stimulation and chemotaxis. Yet, we find that they result in striking differences in activation of the G protein-coupled receptor kinase (GRK)/ß-arrestin system. CCL19 leads to robust CCR7 phosphorylation and ␤-arrestin2 recruitment catalyzed by both GRK3 and GRK6 whereas CCL21 activates GRK6 alone. This differential GRK activation leads to distinct functional consequences. Although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
261
1
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 244 publications
(282 citation statements)
references
References 39 publications
16
261
1
2
Order By: Relevance
“…Thus, we postulate dimer-induced signaling induces a nonmotile cellular idling response. The differential signaling activated by CXCL12 H25R and CXCL12 2 mirrors prior reports for the CCR7 ligands CCL19 and CCL21, as well as monomeric and dimeric forms of CXCL8 (33,34).…”
Section: Discussionsupporting
confidence: 62%
“…Thus, we postulate dimer-induced signaling induces a nonmotile cellular idling response. The differential signaling activated by CXCL12 H25R and CXCL12 2 mirrors prior reports for the CCR7 ligands CCL19 and CCL21, as well as monomeric and dimeric forms of CXCL8 (33,34).…”
Section: Discussionsupporting
confidence: 62%
“…Other studies have shown that β-arrestins and GRK6 are overexpressed in mouse and monkey models of PD (43,44), and that lentiviral-mediated overexpression of GRK6 in rodent and monkey models of PD reduces LIDs (30). GRK6, which lies upstream of β-arrestins in the GPCR signaling cascade, presumably promotes β-arrestin-dependent signaling (45)(46)(47). Therefore, we reasoned that βarr2 might play a critical role in the mechanism of L-DOPA therapy in PD.…”
Section: Resultsmentioning
confidence: 99%
“…CCX-CKR was, however, unable to activate downstream signaling to ERK1/2 and Akt upon stimulation with CCL19, whereas CCL19 activates ERK1/2 in a ␤-arrestin2-dependent manner via CCR7 (38). Importantly, ␤-arrestin can activate numerous other kinases as well as phosphatases in addition to ERK1/2 and Akt (39) and the activation of these additional signal effectors through CCX-CKR remains to be investigated, preferably in physiologically relevant assay systems.…”
Section: Figure 8 Potentiation Of Ccx-ckr-mediated Cre Activation Ismentioning
confidence: 99%